Endometriosis and aspirin: a systematic review - Yang, Yi; Lai, HanHong; Li, ZhengJuan; Zhang, Jun (Frontiers in Endocrinology, 2024)
Introduction Endometriosis is delineated as a benign yet steroid-dependent disorder characterized by the ectopic presence of endometrial glandular and stromal cells outside the uterine cavity, affecting estimated 10%–15% of women of reproductive age, 20%–50% of all women with infertility and costing a great economic burden per-patient. Endometriosis exerts pervasive influence on multiple facets of female reproductive physiology. Given its characterization as a chronic inflammatory disorder, escalated levels of pro-inflammatory cytokines were unequivocally recognized as well-established characteristics of endometriosis, which might attribute to mechanisms like retrograde menstruation, progesterone receptor resistance, and immune dysregulation. Therapeutic utilization of non-steroidal anti-inflammatory drugs (NSAIDs) like aspirin, analgesic agent for reducing pain, inflammation, and fever, could be holding promise in augmenting reproductive outcomes of endometriosis women. Therefore, the objective of this comprehensive review is to elucidate the intricate interplay between endometriosis and aspirin, both within the context of infertility and beyond. We meticulously explore potential pharmacological agents targeting endometriosis, which may concurrently optimize the efficacy of reproductive interventions, while also delving into the underlying mechanistic pathways linking endometriosis with inflammatory processes. Methods We conducted a comprehensive search in the data available in PubMed and the Web of Science using the terms ‘endometriosis’ and ‘aspirin’. Then analyzed the identified articles based on established inclusion and exclusion criteria independently by three reviewers. Results The survey of the chosen terms revealed 72 articles, only 10 of which were considered for review. Discussion Based on the research available currently, it is not substantial enough to address the conclusion that aspirin shall be an effective therapeutic choice for endometriosis, further studies are needed to elucidate the efficacy, safety profile, and optimal dosing regimens of aspirin in the context of endometriosis treatment.